Case-control study of the low intensive autism-specific early behavioral intervention A-FFIP: outcome after one year - Kitzerow, Janina; Teufel, Karoline; Jensen, Katrin; Wilker, Christian; Freitag, Christine M. (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2019)
. Abstracts: Objective: In current international research, early intervention in children with autism-spectrum disorder (ASD) focuses on naturalistic developmental behavioral interventions (NDBI). The manualized Frankfurt Early Intervention Program for preschool-aged children with ASD (A-FFIP) implements NDBI principles within a low-intensity approach of 2 h intervention/week. The present case-control study established effect sizes of change in autistic symptoms, comorbid behavioral problems as well as IQ after one year. Methodology: An intervention group ( N = 20; age: 3.4-7.9 years) and a treatment-as-usual control group ( N = 20; age: 3.2-7.3 years) of children with ASD were matched for developmental and chronological age. The outcome measures used were the ADOS severity score, the Child Behavior Checklist, and cognitive development. Results: After one year, the A-FFIP group showed a trend towards greater improvement in autistic symptoms (η 2 = .087 [95 %-CI: .000-.159]) and significantly greater improvements in cognitive development (η 2 = .206 [CI: .012-.252]) and global psychopathology (η 2 = .144 [CI: .001-.205]) compared to the control group. Conclusion: The efficacy of A-FFIP should be established in a larger, sufficiently powered, randomized controlled study.
Gesehen am 09.04.2020